Mozart and the Wolf Gang - Burgess, Anthony 1917-1993 (London Vintage, 1992)
Mozart and the Wolf Gang brings to life various composers through fictional representations: Prokofiev, Gershwin, Elgar, Rossini, Mendelssohn, Berlioz, Wagner and Schoenberg feature in various dialogues. Among other things, it attempts to fictionalize Mozart's Symphony No. 40.
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; Novel